Constructing masculinity through ulwaluko: a scoping literature review - Mlamli Diko (Cogent Arts & Humanities)
Masculinity and ulwaluko within amaXhosa remain contentious due to two conflicting ideologies. The first one is the construction of male behaviors, attitudes, and identities, and the second one is the obstruction of acceptable cultural norms and values. Ulwaluko, a traditional initiation practice, is fraught with complexities, necessitating ongoing scholarly dialogues. Therefore, this article employs a scoping literature review to unearth how masculinity is constructed through ulwaluko within amaXhosa, an indigenous South African group. At the same time, it addresses central controversies and challenges inherent in this rite of passage, aiming to evoke critical dialogues around these issues. The findings uncover that ulwaluko has historically held socio-cultural, economic, and political significance in constructing amaXhosa male identity. Despite its enduring value in many indigenous African communities today, this cultural practice is profoundly impacted by (post)colonialism and globalisation. Ultimately, this article calls for a balanced discernment of ulwaluko, one that acknowledges its cultural heritage while addressing modern challenges to guarantee its preservation and adaptability in contemporary contexts and beyond.